Properties of oscillatory neuronal activity in the basal ganglia and thalamus in patients with Parkinson’s disease - Du, G. (Transl Neurodegener, 2018)
BACKGROUND: The cardinal features of Parkinson’s disease (PD) are bradykinesia, rigidity and rest tremor. Abnormal activity in the basal ganglia is predicted to underlie the mechanism of motor symptoms. This study aims to characterize properties of oscillatory activity in the basal ganglia and motor thalamus in patients with PD. METHODS: Twenty-nine patients with PD who underwent bilateral or unilateral electrode implantation for subthalamic nucleus (STN) DBS (n = 11), unilateral pallidotomy (n = 9) and unilateral thalamotomy (n = 9) were studied. Microelectrode recordings in the STN, globus pallidus internus (GPi) and ventral oral posterior/ventral intermediate of thalamus (Vop/Vim) were performed. Electromyography of the contralateral limbs was recorded. Single unit characteristics including interspike intervals were analyzed. Spectral and coherence analyses were assessed. Mean spontaneous firing rate (MSFR) of neurons was calculated. Analysis of variance and X(2) test were performed. RESULTS: Of 76 STN neurons, 39.5% were 4–6 Hz band oscillatory neurons and 28.9% were β frequency band (βFB) oscillatory neurons. The MSFR was 44.2 ± 7.6 Hz. Of 62 GPi neurons, 37.1% were 4–6 Hz band oscillatory neurons and 27.4% were βFB neurons. The MSFR was 80.9 ± 9.6 Hz. Of 44 Vop neurons, 65.9% were 4–6 Hz band oscillatory neurons and 9% were βFB neurons. The MSFR was 24.4 ± 4.2 Hz. Of 30 Vim oscillatory neurons, 70% were 4–6 Hz band oscillatory neurons and 13.3% were βFB neurons. The MSFR was 30.3 ± 3.6 Hz. Further analysis indicated that proportion of βFB oscillatory neurons in STN and GPi was higher than that of similar neurons in the Vop and Vim (P < 0.05). Conversely, the proportion of 4–6 Hz band oscillatory neurons and tremor related neurons in the Vim and Vop was higher than that of STN and GPi (P < 0.05). The highest MSFR was for GPi oscillatory neurons whereas the lowest MSFR was for Vop oscillatory neurons (P < 0.005). CONCLUSION: The alterations in neuronal activity in basal ganglia play a critical role in generation of parkinsonism. β oscillatory activity is more prominent in basal ganglia than in thalamus suggesting that the activity likely results from dopaminergic depletion. While both basal ganglia and thalamus have tremor activity, the thalamus appears to play a more important role in tremor production, and basal ganglia β oscillatory activity might be the trigger.